SmMYB113 Is a Key Transcription Factor Responsible for Compositional Variation of Anthocyanin and Color Diversity Among Eggplant Peels - Yang, Guobin; Li, Lujun; Wei, Min; Li, Jing; Yang, Fengjuan (Frontiers in Plant Science, 2022)
To understand the color formation mechanism in eggplant (Solanum melongena L.) peel, a metabolomic analysis was performed in six cultivars with different peel colors. A total of 167 flavonoids, including 16 anthocyanins, were identified based on a UPLC-MS/MS approach. Further analysis revealed that the delphinidins/flavonoids ratio was consistent with the purple coloration of eggplant peels, and SmF3′5′H expression level was consistent with the delphinidin 3-O-glucoside and delphinidin 3-O-rutinoside contents, the main anthocyanins in the purple-peels eggplant cultivars identified in this study. SmMYB113 overexpression promoted anthocyanins accumulation in eggplant peels and pulps. Metabolomic analysis revealed that delphinidins were still the main anthocyanins class in the peels and pulps of SmMYB113-OE4, but most anthocyanins were glycosylated at the 5-position of the B-ring. Our results provide new insights into the anthocyanin composition of eggplant peels and demonstrate the importance of SmMYB113 in stimulating anthocyanin biosynthesis in eggplant fruits.